Methane Emission from Siberian Wet Polygonal Tundra on Multiple Spatial Scales: Process-based Modelling of Methane Fluxes on the Regional Scale, Lena Delta. - Kirschke, Stefanie; Günther, Kurt P.; Wißkirchen, Klaus; Sachs, Thorsten; Dech, Stefan (Institute of Northern Alaska, University of Alaska, 2008)
Uncertainties in the carbon budget of high latitude ecosystems are partly due to difficulties in assessing the spatially and temporally highly variable methane emissions of permafrost soils. CH4 contributes significantly to global warming. Arctic regions are most critically influenced by a changing climate. Modeling approaches are important tools to determine CH4 fluxes of arctic environments. We present two process-based models to calculate methane emission from permafrost soils. Model forcing consists of ECMWF (European Center for Medium-Range Weather Forecasts) meteorological data which are validated against field measurements. Auxiliary input data is derived from satellite imagery and field measurements. A MERIS-FR land classification scheme is used to upscale emissions. Model results are validated using methane flux measurements on the landscape and small scale carried out in 2006 in the Lena Delta (72°N, 126°E) by Alfred Wegener Institute for Polar and Marine Research. The study site is characterized by arctic tundra ecosystems and continuous permafrost.